Incidence rate of depression and factors affecting children and adolescents with type 1 diabetes mellitus (T1DM) in Semarang, Central Java - Fadia Raihani Aprilia Herenda; Tanjung Ayu Sumekar; Agustini Utari; Fanti Saktini (Published by Universitas Gadjah Mada, 2025)
Type 1 diabetes mellitus (T1DM) is characterized by pancreatic ß-cell damage due to an autoimmune process that causes a lack of endogenous insulin production. In 2018, 1,220 children with T1DM was reported in Indonesia. Children and adolescents with T1DM require lifelong insulin treatment leading to diabetes distress and depression. Type 1 diabetes mellitus and psychological problems are bidirectionally interconnected. This study aimed to determine the incidence of depression and influencing factors in children and adolescents with T1DM in Semarang City, Indonesia. This analytical observational study with a crosssectional design was conducted from March to October 2023 at Diponegoro National Hospital and Dr. Kariadi General Hospital, Semarang, using consecutive sampling. The inclusion criteria were children aged 7–17 years diagnosed with T1DM and receiving treatment. Parents of respondents provided informed consent before their children completed the Children’s Depression Inventory (CDI) questionnaire to assess depression. A CDI score of ≥13 was classified as indication of depression. The data were analyzed descriptively and bivariately using Chi-square and Fisher’s exact tests. Among 27 respondents, 8 children were diagnosed with depression and 19 respondents scored on the guilt subscale of the CDI questionnaire, indicating moderate depressive symptoms. Approximately 30% of children and adolescents with T1DM were diagnosed with depression. The most influential factor associated with this depression was a history of chronic disease in children.